Impact of propionic acid-rich diets on microbial composition of the murine gut microbiome - Greenman, Noah; Abdelli, Latifa S.; Hassouneh, Sayf Al-Deen; Ali, Sobur; Johnston, Catherine; Naser, Saleh A.; Azarian, Taj (Frontiers in Microbiomes, 2024)
Propionic acid (PPA), an anti-fungal agent and common food additive, has been shown to induce atypical neurodevelopment in mice, accompanied by gastrointestinal dysfunction potentially resulting from gut dysbiosis. A putative association between dietary PPA exposure and gut dysbiosis is suggested but has not been explored directly. Here, we investigated PPA-associated alteration in gut microbial composition that may result in dysbiosis. Using long-read metagenomic sequencing, gut microbiomes of mice fed an untreated (n=9) or PPA-rich (n=13) diet were sequenced to assess differences in microbial composition and bacterial metabolic pathways. Dietary PPA was associated with an increased abundance of notable taxa, including several species of Bacteroides, Prevotella, and Ruminococcus, whose member species have previously been associated with PPA production. Microbiomes of PPA exposed mice also possessed a greater abundance of pathways related to lipid metabolism and steroid hormone biosynthesis. Our findings demonstrate PPA’s effect in altering the gut microbiota and associated metabolic pathways. These observed changes highlight how preservatives listed as safe for consumption may affect gut microbiome composition with implications for one’s health.